2020
DOI: 10.1021/acs.jpcb.0c05912
|View full text |Cite
|
Sign up to set email alerts
|

Multiphase Behavior of Tetraphenylethylene Derivatives with Different Polarities at High Pressures

Abstract: Although both pressure and temperature are essential parameters governing thermodynamics, the effects of the pressure on solution phase equilibria have not been well studied compared to those of temperature. Here, we demonstrate the interesting pressure-dependent behavior of tetraphenylethylene derivatives in multiphase systems composed of an organic phase and an aqueous phase in the presence and absence of γcyclodextrin (γ-CD). In this system, tetraphenylethylene monocarboxylic acid (TPE1H) and its dicarboxyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…21 Since the hydrostatic pressure effect on the red shi is generally observed as ca. 1 cm À1 MPa À1 in using common organic dyes, [54][55][56][57][58][59][60][61][62][63] the a A values obtained in toluene, chloroform and dichloromethane are reasonably pronounced as the general hydrostatic-pressureinduced spectral change, which means that a particular conformational change in the foldamer skeleton does not occur upon pressurization. Very interestingly, only in acetonitrile, the 0-0 absorption band is quite suppressed under low pressures, compared to the 0-1 band.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…21 Since the hydrostatic pressure effect on the red shi is generally observed as ca. 1 cm À1 MPa À1 in using common organic dyes, [54][55][56][57][58][59][60][61][62][63] the a A values obtained in toluene, chloroform and dichloromethane are reasonably pronounced as the general hydrostatic-pressureinduced spectral change, which means that a particular conformational change in the foldamer skeleton does not occur upon pressurization. Very interestingly, only in acetonitrile, the 0-0 absorption band is quite suppressed under low pressures, compared to the 0-1 band.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, we have recently revealed that optical properties, molecular and biomolecular recognition behavior and photo-physical/chemical processes in solutions of various molecular, supramolecular, macromolecular and biomacromolecular systems are precisely regulated by hydrostatic pressure. [53][54][55][56][57][58][59][60][61][62][63] Hence, these trends prompted us to newly investigate an applicable supramolecular recognition system under hydrostatic pressures.…”
Section: Introductionmentioning
confidence: 99%
“…Fluorescence spectra were recorded on a JASCO FP-8500 spectrofluorometer. All fluorescence experiments were performed by a custom-built high-pressure apparatus (see Figure S1 in the Supporting Information (SI)), and the detailed methods have been described in previous reports in the literature. , Phase-contrast and fluorescence images (Figure d) were captured by a fluorescence microscope (BZ-9000, Keyence) with an objective lens (Plan Fluor EL 20×, Nikon). An excitation filter, a dichroic mirror, and an emission filter for DAPI were 360/40, 400, and 460/50 nm, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…This fact means that precisely controlling equilibria/rates seems to be quite difficult from the sensitive entropy drift’s perspective. , On the other hand, one notices that a pressure regulation, rather than the enthalpy–entropy combination, may undoubtedly be better for precise control based on eq . Indeed, it is well-known that hydrostatic pressure as one of the isotropic mechanical forces can manipulate not only ground-state equilibria in biomacromolecular conformational changes and artificial host–guest systems but also excited-state rates in photophysical properties and photoreactions. Recently, we have also demonstrated that colorimetric, fluorimetric, and chiroptical properties of functional chromophores are notably controlled by hydrostatic pressurization. Hence, these statements indicate the evident importance of hydrostatic pressure regulation for broad chemical and/or biological events.…”
Section: Introductionmentioning
confidence: 94%
“…The reversible process of assembly and disassembly through host–guest interactions , has emerged as a powerful and flexible strategy to assemble supramolecular structures and attracted interest in optical sensing and imaging, drug and gene delivery, and so on. ,, Cyclodextrins (CDs), a class of cyclic oligosaccharides, are extensively employed as host building blocks owing to their hydrophobic cavities and hydrophilic exteriors, facilitating the formation of inclusion complexes with some hydrophobic guest molecules (for example, adamantine derivatives) in aqueous media . Therefore, the hydrophobic molecules could become more hydrophilic or disperse once the host–guest complexes with CDs in aqueous solutions are formed, which may be used to tune the aggregation and fluorescence of AIE molecules. , For example, Tang et al engineered a γ-CD-TPE host–guest inclusion complex, resulting in the disaggregation of TPE and no fluorescence in water . Multiple host–guest inclusion complexes linked by spacers with or without bulky end-caps could form stable polyrotaxanes (PRs) and polypseudorotaxanes (PPRs).…”
Section: Introductionmentioning
confidence: 99%